More than Just Size: Challenges and Opportunities of Hybrid Dendritic Nanocarriers - Noe Rimondino, Guido; Oksdath-Mansilla, Gabriela; Brunetti, Veronica; Cristina Strumia, Miriam (Current Pharmaceutical Design, 2017)
Background: Dendrimers and hyperbranched polymers are emerging polymer architectures that attract increasing attention due to their unique topological structure and interesting physicochemical properties. Their enormous potential makes them particularly attractive to form new and fascinating nanometric drug delivery systems, solving several typical shortcomings encountered in nanomedicine. Objective: In this context, the recent developments of dendritic and hyperbranched based systems, together with their application as nanocarriers, have been comprehensively reviewed. Conclusion: This review highlights how the structural complexity can be taken as an evolution parameter of these nanosystems, starting with hyperbranched polymers and evolving to more complex structures such as hybrid dendritic-inorganic nanoparticles and dendronized nano-objects hierarchically designed. Finally, future directions and perspectives in this promising field are briefly discussed.
Keywords: hybrid nanoparticles